The Impact of Social Media Marketing on Customer Loyalty: The Mediating Role of Brand Awareness in Skintific Products - Ardhya Arifah Zahro; Ratih Hurriyati; Puspo Dewi Dirgantari; Francis Kortey Mac-Doqu (Sinergi International Journal of Management and Business, 2026)
The skincare industry in Indonesia is growing rapidly, with Skintific becoming one of the popular brands among young consumers. This study investigates the effect of social media marketing on customer loyalty among 157 Skintific users in Bandung, specifically testing the mediating mechanism of brand awareness. The analysis was conducted using Hayes’ PROCESS. Model 4 in SPSS 26, employing bootstrapping to validate the indirect effects. The result show social media marketing have a positive effect on brand awareness and customer loyalty, with brand awareness playing a significant mediator. This study fills in the gaps in previous studies on the role of brand awareness in the relationship between social media marketing and customer loyalty, using the PROCESS Hayes Model 4. The R2 value for the brand awareness model was 0.7046 and the customer loyalty model was 0.8090 showed that the independent variables in this study were able to explain the variation of 70.46% and 80.90% of the dependent variables, respectively. These results confirm that the research model has a very strong explanatory power (excellent) of the phenomenon being studied. Previous research has said that social media marketing has no effect on customer loyalty but this study fills a gap in previous research that social media marketing will increase customer loyalty by adding brand awareness mediation. Social media marketing is an important strategy to build customer loyalty, especially through increasing Fbrand awareness. Brands must optimize creative content on social media to maintain loyalty in a competitive market.